The link between cytogenetics/genomics and imaging patterns of relapse and progression in patients with relapsed/refractory multiple myeloma: A pilot study utilizing 18f-fdg pet/ct - Zhou, Xiang; Dierks, Alexander; Kertels, Olivia; Samnick, Samuel; Kircher, Malte; Buck, Andreas K.; Haertle, Larissa; Knorz, Sebastian; Boeckle, David; Scheller, Lukas; Messerschmidt, Janin; Barakat, Mohammad; et al. (Cancers, 2020)
Utilizing 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT), we performed this pilot study to evaluate the link between cytogenetic/genomic markers and imaging patterns in relapsed/refractory (RR) multiple myeloma (MM). We retrospectively analyzed data of 24 patients with RRMM who were treated at our institution between November 2018 and February 2020. At the last relapse/progression, patients had been treated with a median of three (range 1–10) lines of therapy. Six (25%) patients showed FDG avid extramedullary disease without adjacency to bone. We observed significantly higher maximum standardized uptake values (SUVmax) in patients harboring del(17p) compared with those without del(17p) (p = 0.025). Moreover, a high SUVmax of >15 indicated significantly shortened progression-free survival (PFS) (p = 0.01) and overall survival (OS) (p = 0.0002). One female patient exhibited biallelic TP53 alteration, i.e., deletion and mutation, in whom an extremely high SUVmax of 37.88 was observed. In summary, this pilot study suggested a link between del(17p)/TP53 alteration and high SUVmax on 18F-FDG PET/CT in RRMM patients. Further investigations are highly warranted at this point.
CRIS-Team Scopus Importer:2023-03-23
Keywords: 18F-FDG PET/CT; Multiple myeloma; Pattern1. Introduction; Progression; Radiogenomics; Relapse